Polyhydroxylated azetidine iminosugars: Synthesis, glycosidase inhibitory activity and molecular docking studies. Issue 23 (1st December 2017) - Lawande, Pravin P.; Sontakke, Vyankat A.; Kumbhar, Navanath M.; Bhagwat, Tanay R.; Ghosh, Sougata; Shinde, Vaishali S.
Graphical abstract: Abstract: An efficient and practical strategy for the synthesis of unknown azetidine iminosugars (2 S, 3 R, 4 S )-2-(( R )-1, 2-dihydroxyethyl)-3-hydroxy-4-(hydroxymethyl)azetidine2, (2 S, 3 r, 4 R )-3-hydroxy-2, 4-bis(hydroxymethyl)azetidine3 and (2 S, 3 R, 4 S )-3-hydroxy-4-(hydroxymethyl)- N -methylazetidine-2-carboxylic acid4, starting from thed -glucose has been reported. The methodology involves preparation of the 3-amino- N -benzyloxycarbonyl-3-deoxy-6- O - tert -butyldimethylsillyl-1, 2- O -isopropylidene- α -d -glucofuranose9, which was converted to the C-5- OMs derivative11 . Intramolecular nucleophilic displacement of the C-5- OMs group with in situ generated 3-amino functionality provided the required key azetidine ring skeletons10 with additional hydroxymethyl group. Removal of 1, 2-acetonide protection, followed by reduction and hydrogenolysis afforded azetidine iminosugar2 . Alternatively, removal of 1, 2-acetonide group and chopping of C1-anomeric carbon gave C2-aldehyde that on reduction or oxidation followed by hydrogenolysis gave 2, 4-bis(hydroxymethyl) azetidine iminosugars3 and N -methylazetidine-2-carboxylic acid4 respectively. The glycosidase inhibitory activity of2 –4 iminosugars was screened against various glycosidase enzymes and compared with a standard miglitol. Amongst synthesized targets, the compound2 was found to be more potent amyloglucosidase inhibitor than miglitol. These results were supported by molecular docking studies.